A CDC42 Homologue in Claviceps purpurea Is Involved in Vegetative Differentiation and Is Essential for Pathogenicity - Scheffer, Jan (American Society for Microbiology, 2005)
Claviceps purpurea, a biotrophic pathogen of cereals, has developed a unique pathogenic strategy including an extended period of unbranched directed growth in the host's style and ovarian tissue to tap the vascular system. Since the small GTPase Cdc42 has been shown to be involved in cytoskeleton organization and polarity in other fungi, we investigated the role of Cdc42 in the development and pathogenicity of C. purpurea. Expression of heterologous dominant-active (DA) and dominant-negative (DN) alleles of Colletotrichum trifolii in a wild strain of C. purpurea had significant impact on vegetative differentiation: whereas DA Ctcdc42 resulted in loss of conidiation and in aberrant cell shape, expression of DN Ctcdc42 stimulated branching and conidiation. Deletion of the endogenous Cpcdc42 gene was not lethal but led to a phenotype comparable to that of DN Ctcdc42 transformants. ΔCpcdc42 mutants were nonpathogenic; i.e., they induced no disease symptoms. Cytological analysis (light microscopy and electron microscopy) revealed that the mutants can penetrate and invade the stylar tissue. However, invasive growth was arrested in an early stage, presumably induced by plant defense reactions (necrosis or increased production of reactive oxygen species), which were never observed in wild-type infection. The data show a significant impact of Cpcdc42 on vegetative differentiation and pathogenicity in C. purpurea.